The Proximate Analysis and Sensory Hedonic Evaluation of Energy Drink (Agarbomb) - Ahmad Lutfy, Siti Nuruljannah; Saad, Abul Khair; Zakaria, Nazri; Md Nor, Norazmir (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2024)
The main purposes of this study are to assess the consumers' acceptance of the sensory attributes of energy powder made from guarana as caffeine and to determine the nutritional values of energy powder made from guarana as a substitute for coffee. The method used to conduct this research is measuring proximate analysis of ash, moisture, protein, fat, and crude fibre to identify energy powder's nutrient content. Besides, it discovers the acceptance of energy drinks towards potential consumers by undergoing a 7-point hedonic sensory evaluation test of 25 semi-panels. The outcomes gained from this research are low protein, low fat, and high minerals due to the high ash content, presenting that it is acceptable for energy drinks since it usually focuses on total energy and sugar for energy boost. The panellist's acceptance is concentrated in viscosity and colour, which might concern Agarbomb’s improvement in aroma, taste, and overall acceptability.